2008
DOI: 10.1165/rcmb.2007-0406oc
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Expression by Tumor Suppressor Protein p53

Abstract: Lung carcinoma (H1299) cells deficient in p53 (p53(-/-)) express large amounts of urokinase-type plasminogen activator (uPA) protein and uPA mRNA, and exhibit slower degradation of uPA mRNA than that of p53-expressing nonmalignant Beas2B human airway epithelial cells. Expression of p53 protein in H1299 cells, upon transfection with p53 cDNA, suppressed basal as well as uPA-induced expression of uPA protein in both conditioned media and cell lysates, and decreased the level of steady-state uPA mRNA primarily du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…To clarify if LPS treatment alters p53-induced inhibition of uPA expression, we exposed naïve p53-deficient cells or p53-deficient cells transfected with vector DNA or p53 cDNA to PBS, LPS or the amino-terminal fragment (ATF) of uPA for 24 h. The conditioned media were analyzed for uPA by Western blotting. Consistent with our earlier report, (26) reintroduction of p53 in p53-deficient cells inhibited uPA expression. However, treatment with either LPS or ATF, which mimics full length uPA in terms of uPA expression, partially reversed the inhibitory effects of p53 (Fig 6C).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To clarify if LPS treatment alters p53-induced inhibition of uPA expression, we exposed naïve p53-deficient cells or p53-deficient cells transfected with vector DNA or p53 cDNA to PBS, LPS or the amino-terminal fragment (ATF) of uPA for 24 h. The conditioned media were analyzed for uPA by Western blotting. Consistent with our earlier report, (26) reintroduction of p53 in p53-deficient cells inhibited uPA expression. However, treatment with either LPS or ATF, which mimics full length uPA in terms of uPA expression, partially reversed the inhibitory effects of p53 (Fig 6C).…”
Section: Resultssupporting
confidence: 93%
“…We recently reported that tumor suppressor protein, p53 inhibits uPA expression through destabilization of uPA mRNA. (26) The process involves sequence specific interaction of p53 with a 35 nucleotide destabilization determinant present in the uPA mRNA 3′UTR. Previous studies (2728) suggested that p53 and RRM2 directly interact to control ribonucleotide reductase activity during DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms were therefore proposed; p53 may negatively regulate uPA promoter by interaction with remote enhancer binding factors (Kunz et al, 1995) or p53 may directly bind to the uPA mRNA 3 0 -UTR (Shetty et al, 2008). This study provides another explanation that p53 may act through miR-23b to regulate uPA in human cervical cancer as p53 knockdown reduces miR-23b expression and elevates uPA expression in SiHa cells (data not shown).…”
Section: Hpv-16 E6 Downregulation Of Mir-23b CL Au Yeung Et Almentioning
confidence: 80%
“…67 PAI-1 expression is disproportionately increased in injured lungs 33 and also induced by TGF-b, 23 which in turn irreversibly suppresses both uPA activity and its steady-state level by PAI1emediated turnover of the uPAeuPAR complex. The protective effects of increased uPA and uPAR may involve suppression of PAI-1 through increased uPA-and uPARmediated turnover of PAI-1 protein, 47 or inhibition of p53 expression and reversal of p53-mediated induction of PAI-1 expression by increased uPA and uPAR, 7,44,51,52 or both.…”
Section: Upa-fibrinolytic System In Atii Cell Emtmentioning
confidence: 99%